Aspect and modality in Indonesian; The case of "sudah", "telah", "pernah", and "sempat" - Grangé, Philippe (Wacana, Journal of the Humanities of Indonesia, 2010)
In this paper, I describe four Indonesian aspect markers, sudah, telah, pernah, and sempat, showing that the main opposition between them relies not only on their aspectual meanings, but also on the various modalities they express. The opposition between the very frequent markers sudah and telah is analysed in detail. The syntactic and semantic survey shows that these two markers are not synonyms in most contexts.